Monitoring plant and animal populationtions (Blackwell Science, 2001)
Monitoring Plant and Animal Populations offers an overview of population monitoring issues that is accessible to the typical field biologist and land managers with a modest statistical background. The text includes concrete guidelines for ecologists to follow to design a statistically defensible monitoring program. User-friendly, practical guide, written in a highly readable format. The authors provide an interdisciplinary scope to address the current, widespread interest in monitoring in many environmental fields, including pure and applied ecology, conservation biology, and wildlife management. Emphasizes the role of monitoring in adaptive management. Defines important terminology and contrasts monitoring with other data-collection activities. Covers the applicable principles of sampling and shows how to design a monitoring project. Provides a step-by-step overview of the monitoring process, illustrated by flow charts and references. The authors also offer guidelines for analyzing and interpreting monitoring data...